Microplane model of cylindrical geometry for transversely isotropic polymer composites. (August 2022) - Sabounchi, Saeed; Caner, Ferhun C.
Highlights: A computational microplane model bridging mesoscale inelastic fracture to macroscale fracture is presented. The model is for predicting the inelastic material behavior in 3D stress. The model is formulated to be more intuitive than the spectral microplane model. An explicit algorithm for the model is developed and coded into a VUMAT subroutine. The computational cost of the model is much less than that of competing mesoscale ones. Abstract: In this paper, a microplane model based on cylindrical geometry where the cylinder axis coincides with the longitudinal direction is developed for a general 3D inelastic fracturing analysis by finite element method of transversely isotropic fiber reinforced polymer composites. The model bridges the mesoscale material behavior to macroscale one using the stress equilibrium approach developed for cylindrical geometry. To this end, Microplane level stress–strain relations for tension, compression and shear for both longitudinal and transverse directions are formulated. An explicit algorithm is formulated and coded into a VUMAT user subroutine for use with ABAQUS. The model is suitable for the analysis and design of large structures made of fiber reinforced polymer composites unlike the competing mesoscale models because of its much lower computational cost. A detailed metodology for the calibration of the model is identified. The model is calibrated against the common test data available in the literature using this metodology and the predictive capacity of the model is demonstrated by comparing the model predictions with test data in longitudinal tension, lateral tension, longitudinal compression, lateral compression, longitudinal shear and rare size effect in bending tests including post-peak fracture available in the literature.